Carbon nanotubes vs graphene nanoplatelets for 3D-printable composites. (March 2019) - Gorokhov, G.; Bychanok, D.; Meisak, D.; Shlyk, I.; Liubimau, A.; Angelova, P.; Menseidov, C.; Ivanov, E.; Kotsilkova, R.; Casa, M.; Ciambelli, P.; Kuzhir, P.
Abstract: Polymer-based composites with nanocarbon fillers are of great interest for the wide application range including the needs of wireless communication and the development of precise measuring means and medical devices. However, the composite properties such as excellent electromagnetic energy dissipation or tailorable conductivity are not enough to solve practical problems in engineering. To be fully applicable, the composite material must be low-cost and suitable for conventional methods of fabrication, for example 3D-printing. In current research the electromagnetic properties of PLA-based composites with graphene nanoplatelets and multiwall carbon nanotubes were investigated in microwave frequency range. The synergistic effect of two fillers was observed, the investigated materials proved to be prospective for 3D-printable composite production for electromagnetic applications such as fabrication of complex geometry microwave shields and antennas.